Knowledge Management For SMEs In Developing Countries - Hussain, Iftikhar; Si, Steven; Ahmed, Adnan (Journal of Knowledge Management Practice, 2010)
Knowledge management helps in increasing productivity, effectiveness and efficiency in operations. Overlooking KM can seriously hamper the growth and prosperity of a SME. A comprehensive literature study was undertaken. The study accessed the status of KM in SMEs in developing countries and also examined the factors that influence the adoption of KM for SMEs in developing countries. Many organizations have profited from KM because they recognize the importance of the KM in business growth and development. However the study found SMEs, in developing countries have not realized this importance and still are vulnerable. The study takes this factor into consideration and proposed a KM approach specific to SMEs in developing countries. The study contributes on KM and SMEs literature in developing countries and is one of the few studies conducted in developing countries.
Keywords: Knowledge management; SME; Developing countries; Organization